2021
DOI: 10.3389/fcell.2021.772211
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Signaling of Cancer Stem Cells During Inflammation

Abstract: Malignant tumors pose a great challenge to human health, which has led to many studies increasingly elucidating the tumorigenic process. Cancer Stem Cells (CSCs) have profound impacts on tumorigenesis and development of drug resistance. Recently, there has been increased interest in the relationship between inflammation and CSCs but the mechanism underlying this relationship has not been fully elucidated. Inflammatory cytokines produced during chronic inflammation activate signaling pathways that regulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 125 publications
(142 reference statements)
0
8
0
Order By: Relevance
“…CSCs are the key drivers of cancer and play a role in relapse, resistance to anticancer therapies, and tumor recurrence [ 32 ]. CSCs derived from breast cancer cells with CD44+/CD24 low/− phenotype have the ability of heterogeneous differentiation, initiating diverse tumors and forming mammospheres [ 33 , 34 , 35 , 36 ]. The mammosphere formation assay has been used as a useful method for studying stem cell-like characteristics in breast cancer cell cultures [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSCs are the key drivers of cancer and play a role in relapse, resistance to anticancer therapies, and tumor recurrence [ 32 ]. CSCs derived from breast cancer cells with CD44+/CD24 low/− phenotype have the ability of heterogeneous differentiation, initiating diverse tumors and forming mammospheres [ 33 , 34 , 35 , 36 ]. The mammosphere formation assay has been used as a useful method for studying stem cell-like characteristics in breast cancer cell cultures [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes occur simultaneously with oncogenic events in cancer progression. In GBM, epigenetic modification including DNA methylation, histone modification, and non-coding RNA regulation could modulate the inflammatory genes-oncogenes loop and associated immunosuppression (92)(93)(94)(95), providing a therapeutic strategy and comprehensively recognized pathogenesis of GBM by targeting the inflammatory TME (Table 1).…”
Section: Epigenetic Regulations Of the Inflammatory Microenvironment ...mentioning
confidence: 99%
“…Studies suggested that epigenetic regulation exerts a pivotal role in many diseases such as cancers and CVDs ( Liu et al, 2021 ; Yang et al, 2021 ). Distinct from genetic alteration, epigenetic modification is reversible, and the inhibitor of epigenetic alteration provides a novel insight into searching pharmaceutical therapeutic targets ( Pons et al, 2009 ).…”
Section: Epigenetic Regulation Of Atherosclerosismentioning
confidence: 99%